(3CQHYhf MOjkKG aj aVd GdYOds - (3CMeO Hf MLQ GdTGaYjs
(3ChdgG (B:s
(3GdMeO ddg eGdc Gdedc Pi GdLdGd hGdEcQGe CeG HYO ajbhd CVYa GdhQi CMeO Hf MLQ Ef Gddg jCeQ HGdYOd hGdGMSGf hCf GJMa MVQJg GdSfI HCQHYjf MOjKkG ef cdGe fHjfkG Udi Gddg Ydjg hSde HCSGfjOgG GdeJUdg s
(3BNQgG (B:s
(3abGd dg EfeG aYdJ Pdc EcQGekG dMOjK QShd Gddg Udi Gddg Ydjg hSde abGd dg GcQeJ adGfkG ef GLd EfJSGHg dMOjKi hJMjJge ajgG SdGe hBNQ OYhGge Cf GdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3djOf s
Keywords: (3GdMOjK h GdeUWdMs